Globalization, inequality and social injustice: implications on education and adult education (Innovaciones Educativas, 2024)
Inequality and social injustice have destroyed confidence in human nature by creating shameful gaps that touch upon sociocultural, economic, environmental, spiritual, and political aspects that undoubtedly impact learning processes. The aim of this paper is to explore significant aspects of globalization, inequality and social injustice and their impact on education and adult education. Framed within a general qualitative framework, this paper has adopted an exploratory methodology that intends to provide an in-depth understanding of the phenomenon. This paper offers a critical and reflexive position aiming at raising a significant level of awareness in an attempt to promote and generate reflection spaces that help in the diminution of social injustices and inequalities in our globalized societies within an educational lens. First, globalization is discussed. Obviously, globalization has brought the world together in a spiral of knowledge, technology, and information. Next, inequality in education is explored: residential schools, the prevalence of racism and the systematic invisibility of minority groups. Additionally, social injustice and movements in adult education are also considered: the Antigonish movement, the frontier college, and the no movement against Central America Free Trade Agreement (CAFTA). It is a foregone conclusion that inequality and social injustice have had a tremendous impact on societies and learning settings as well. Finally, neoliberal policies have promoted a very noticeable savage economic Darwinism that privileges commodification, privatization and a public pedagogy that focuses on entrepreneurial subjects.
Keywords: globalization; inequality; social injustice; social movements; education; learning process